Application of alkali-treated MCM-22 zeolite in catalytic 1-decene oligomerization reaction. (15th July 2023) - Gong, Fuqing; Liu, Naiwang; Shi, Li; Meng, Xuan
Graphical abstract: Highlights: Production method for replacing conventional homogeneous catalysts with the environmentally friendly MCM-22 zeolite. The conversion of 1-decene was increased from 68% to 76% and the dimer selectivity was increased from 49% to 61%. Alkali treatment introduces mesopores in MCM-22 zeolite to increase the amount of surface acid and improve activity. The presence of the stencil agent hinders the desilication process of the MCM-22 zeolite after alkali treatment. Abstract: It was found that the MCM-22 zeolite was highly active in catalyzing the oligomerization of 1-decene. The conversion rate and dimer selectivity increased with the increasing time of NaOH treatment. When MCM-22 zeolite was treated with a 0.1 mol/L NaOH solution for 7 h, conversion increased from 68% to 76% and dimer selectivity increased from 49% to 61%. The catalyst could be reused three times. After TG analysis, the catalytic effect after regeneration by roasting at 550 °C was no different from that of fresh catalyst. The composition, acidity, structural properties, and pore structure of MCM-22 zeolites before and after alkali treatment were investigated by Py-IR, N2 adsorption-desorption, ICP, 1-decene adsorption, XRD, SEM, and 29 Si NMR. After NaOH treatment, the MCM-22 zeolite stripped the skeletal Si atoms, introduced mesopores, increased the concentration of strong Brønsted and Lewis acid sites, and showed better catalytic performance in the 1-decene oligomerization reaction.